Aplicação da multa do Art. 461 do Código de Processo Civil em mandado de segurança - Okajima, Sílvia Sayuri (2014)
The present study aims at the discussion on the application of the fine provided for in art. 461 of the Code of Civil Procedure in an injunction. To develop the theme initially examines relevant aspects of specific performance of the obligations of do's and don'ts, the coercive fine art. 461 of the CPC and the injunction to the analysis of such institutes, concluded by the application or not of "daily fine" art. 461 of the Code of Civil Procedure to the injunction